Analisis Akuntabilitas Dan Transparansi Laporan Keuangan Pada Panti Asuhan Seraphine Kecamatan Katikutana Kota Waibakul - Melania Rambu Guna; Khojanah Hasan; Dwi Anggarani (Jurnal Akuntansi Keuangan dan Bisnis, 2025)
Orphanage, Katikutana District, Waibakul City, is a non-profit organization engaged in social work. The purpose of this study was to analyze the accountability and transparency of financial reports at Seraphine Orphanage. The research method used was a descriptive qualitative method with a case study approach. Data collection techniques included observation, interviews, and documentation. The results showed that the analysis revealed inadequate accountability and transparency practices implemented by the management of Seraphine Katiku Loku Orphanage. This is reflected in process accountability, program accountability, policy accountability, financial accountability, and transparency.